Kajian Teologis Film Drama Romantis Dalam Perspektif Wawasan Dunia Kristen - Aswan Aswan; Tony Salurante (Sekolah Tinggi Teologi Internasional Harvest Tangerang, 2023)
The media currently plays an important role, one of which is the entertainment media for romantic drama films. Romantic drama films are one of the most popular genres of various age groups. Its presence, which can be enjoyed by various age groups, can cause problems, including for believers. Not infrequently the film presents messages or values that are contrary to religious beliefs. This research answers the question how does the Christian worldview evaluate the romantic genre film? There are many messages from various films circulating in Indonesia that need to be studied. In this context, theological study can be an attempt to analyze the messages and values contained in romantic drama films by using the concept of a Christian worldview. The research method used is descriptive qualitative with a Christian worldview approach. This concept refers to a world view based on Christian religious beliefs, which can help believers understand the moral and spiritual values contained in films. This research shows that various films of the romantic genre from within the country and abroad can influence Christian culture sooner or later to move away from practical theological values. This does not cause someone to stay away from watching that movies.